Detection of Helicobacter pylori infection of the gastric mucosa by measurement of gastric aspirate ammonium and urea concentrations. Issue 9 (September 1991) - Neithercut, W D; Milne, A; Chittajallu, R S; el Nujumi, A M; McColl, K E
Abstract : Helicobacter pylori possesses unusually high urease activity that lowers the urea concentration and raises the ammonium concentration of the gastric juice in infected people. The value of measuring urea and ammonium concentrations in gastric juice obtained during upper gastrointestinal endoscopy as a means of diagnosing the presence and eradication of the infection was assessed. Twenty four subjects with the infection and 14 in whom it had been eradicated were examined. Their H pylori status was confirmed by antral biopsy and 14C urea breath test. The median (range) gastric juice urea concentration in infected subjects was 0.8 mmol/l (0.5-2.9 mmol/l), which was lower than that in the uninfected subjects (2.1 mmol/l (1.0-3.7 mmol/l)) (p less than 0.001). The median gastric juice ammonium concentration in infected subjects was 3.4 mmol/l (1.0-13.0 mmol/l), which was higher than that in the uninfected subjects (0.64 mmol/l (0.02-1.4 mmol/l)) (p less than 0.001). Though the two groups overlapped in respect of their urea and ammonium concentrations, they were completely different when the urea: ammonium ratios were calculated--the ratios ranged from 0.04-0.7 (median 0.26) and from 1.1-113 (median 3.4) in infected and uninfected subjects respectively (p less than 0.001). Treatment with H2 antagonists did not change the concentrations of urea and ammonium or their ratio in gastric juice. Measurement of the urea: ammonium ratio in aspirated gastric juice obtained during routine upper gastrointestinal endoscopy may provide a rapid method of detecting H pylori infection and of confirming its eradication.